Using prescribed fires in young forests: A pyrosilvicultural approach - Hunter Noble; Robert A. York (California Agriculture)
Prescribed burning is an effective treatment to reduce the risk of very severe wildfires. Many forests, however, are ill-suited for prescribed fire, because of high fuel loads, high tree densities, or young stands that are vulnerable to low intensity fires. Utilizing prescribed fire in reforested stands established after high-severity fires can protect against further losses from subsequent wildfires (“reburn” fires). Only a handful of studies provide practical guidance on how and when to burn young forests. We apply the concept of “pyrosilviculture” to suggest ways in which pre-fire silvicultural treatments can make prescribed burns more effective across a variety of age classes and structures. We also update results from a study in which several age classes of stands (12-, 22-, 32-, and 100-year-old) were burned experimentally on the same day. This focuses on a key question for managers: how to determine the right stand age at which prescribed fires may become feasible. As expected, older stands were more resistant to damage and had higher survival rates. If tree survival during prescribed fires is a primary objective, then a conservative approach is to wait until stands are age 30 before instituting prescribed fire. This is likely an overestimate of the minimum age, given that the prescribed fires applied in this study occurred during especially dry conditions. Under different objectives, higher mortality may be considered beneficial if it creates low-density, high-complexity stands that are similar to historic conditions.